A study of the stangnant zone on cutting edges of HSS - 376496 Goh, Tee Lee (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006